TRANSFORMING THE SHAPE OF THE BETAWI ONDEL-ONDEL AND GIGI BALANG ICONS USING THE QUILT APPLICATION TECHNIQUE: THE ALUMNI COMMUNITY OF TARAKANITA IV MIDDLE SCHOOL - Asih Retno Dewanti; Zoya Natalia Kasim; Tasya Wira Cahyani (Bajang Institute, 2025)
Community Service Activities are an extension of the Regional Government's efforts to introduce the creative economy to the community so that they can become economically independent. The Faculty of Fine Arts and Design took part by carrying out a PkM entitled Transformation of the Betawi Icon 'Ondel-ondel' and the Lisplang 'Gigi Balang' Shape for Tarakanita IV Alumni, Rawamangun - Jakarta who had entered retirement age. This activity utilizes fabric waste from the remainder of the Home Sewing industry to be reprocessed into new forms that have aesthetic value and sold using the Quilt Technique with the resulting products being chair cushion covers and Placemats. The aim of this activity can be an effort to fill free time during retirement while still being able to socialize by doing something that can become a business opportunity and increase income